Mahakal Blessed My Crop: Community Dynamics and Religious Beliefs Influence Efficacy of a Wildlife Compensation Program - Kshettry, Aritra; Bhave, Nupur; Das, Priyanka; Athreya, Vidya (Frontiers in Conservation Science, 2021)
Conservation conflicts or human-wildlife conflicts present one of the foremost challenges to wildlife conservation globally. The challenges of reconciling human safety and food security with the conservation of large-bodied wildlife are further compounded in developing nations with a high spatial overlap of wildlife with people. Therefore, conservation models are required to offset losses faced by affected communities while at the same time ensuring the long-term conservation of wildlife species in shared spaces. Ex-gratia payment is one such widely used conflict mitigation instrument that aims to offset losses and increase tolerance towards damage-causing wildlife species. However, the efficacy of such programs is rarely investigated and the complex interplay of local beliefs, traditions, and community dynamics are rarely incorporated in compensation programs. In this paper, we study an ex-gratia payment program for crop losses in India using ecological, economic as well as social lenses. We use 119 interview surveys across 30 villages. Linear models and thematic analysis were to understand the sources of crop losses, the propensity to claim ex-gratia payments, and the reasons for claiming or not claiming. We find that even though wildlife is the major cause of crop loss in the region, especially to elephants, the majority of the respondents (53%) did not claim compensation for losses. The reasons varied from procedural failures to a negative evaluation of the process or the agency involved but the most recurrent reason for not claiming was a deep religious belief in certain communities on the elephant God, ‘Mahakal’. Our work indicates that cultural reverence towards the species is enabling the acceptance of losses. We propose that such complex cultural beliefs and local traditions should be kept in mind when designing schemes that aim to garner conservation support towards damage-causing wildlife species.